(3QSGdI aj YOe JbQjQ Cgd GdPeI aj Gdjef ef GdHdfjGf hZjQge ef Cgd GdPeIs - (3GdMSf Hf CMeO GdLdGds ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3GdMeO ddg hSdGeg Ydi YHGOg GdPjf EUWai SCdJ CQTOfG Gddg hEjGc Yf JbQjQ GdHdfjGf ai Gdjef s
(3BNQgG (B:s
(3HYO GdEWdGY YdieG HjfGg hef cGf ePgHg bHhd UMjM GdSfI hYOe fSN BjI GdSja hbO bOefG JaUjd Pdc hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO hBdg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdeLGejYs